Leonardo da Vinci [videorecording (DVD)] - Shaw, Caroline (Caroline Adelaide) (PBS, 2024)
The film will tell the story of Leonardo di ser Piero da Vinci, best known as Leonardo da Vinci, a fifteenth century Italian polymath of soaring imagination and profound intellect, who left behind artistic works of staggering beauty and detailed sketches of futuristic contraptions of warfare and flight that today are marveled at for their technical ingenuity and foresight. From his birth out of wedlock to a notary and peasant woman and apprenticeship to a distinguished Florentian painter, to his days as a military architect, cartographer, sculptor and muralist for hire, the film will offer an intimate portrait of a singular visionary whose Mona Lisa, The Last Supper and The Vitruvian Man are among the most celebrated works known to man, but whose artistic endeavors sometimes seemed an afterthought to his pursuits in science and engineering.